Membrane fouling reduction prospects in membrane separation plants: Release coatings and nanomaterials - Ilinykh, A. S.; Naschetnikova, O. B.; Migalatiy, E. V. (AIP conference proceedings, 2023)
The use of the advanced membrane separation plants for water treatment and wastewater treatment allows achieving high quality water treatment. However, in the process of operation of the units, additional problems associated with membrane fouling such as formation of a layer of sludge on the membrane surface arise. In this paper the authors tried to consider methods of non-reagent control of membrane fouling in membrane separation plants, in particular the use of anti-adhesion coatings and nanomaterials. In recent years, the attention of many researchers has been focused on the use of nanomaterials. For mitigation of membrane fouling, several nanomaterials, which showed the effectiveness of nanotechnology in solving the membrane fouling problem, were considered. Nevertheless, the results of the review show that the use of only one method to control membrane fouling is insufficient; it is necessary to use complementary, already existing approaches. The large-scale application of both fouling reduction methods discussed in the review should be the subject of future studies. Also, the application of two different anti-fouling approaches (active or passive) in addition to the study of new nanomaterials should be the focus of future research. In addition, the issue of overcoming the trade-off between anti-fouling properties and permeability of the membrane surface, as well as studying the stability of the use of anti-fouling techniques that reduce membrane contamination, remains open.